Corporate Social Responsibility in the Maritime Industry (Cham : Springer International Publishing, 2018)
This book addresses the environmental, legal, social, and economic aspects of corporate social responsibility in the maritime industry. It discusses the voluntary aspects of the CSR concept and how the lines between informal and formal rules are merging and becoming fuzzy. Further, it shows how regulation is enhancing responsibility and sustainability in the maritime industry. The book gathers the experiences of the WMU, IMO, UN and public and private actors in developing and developed countries in the maritime industry.
Lisa Loloma Froholdt, Introduction -- Lisa Loloma Froholdt, The perception of Corporate Social Responsibility in the maritime industry -- Devinder Grewal, The Growth of CSR and its Acceptance in the Maritime Industry -- Yoshinobu Takei, Governance of Maritime Activities: Legal, Policy and Institutional Aspects -- Patrick Donner, George Theocharidis and Tafsir Johansson, Methods to Promote Improved Governance in Maritime Administrations of Developing Nations -- Momoko Kitada and Lise Synnøve Neeraas Langåker, Arctic Governance and Gender: Climate Change or Social Change? -- Neil Bellefontaine and Tafsir Johannson, Effective and Efficient Maritime Administration & Corporate Social Responsibility -- Aykut I.Ölçer and Fabio Ballini, Energy Management in the Maritime Industry -- Patrick Donner and Tafsir Johansson, Sulphur Directive, Short Sea Shipping & Corporate Social Responsibility in a EU Context -- D.S.H. Moon, J.K. Woo and T.G. Kim, Green Ports and Economic Opportunities -- Michael Baldauf, Knud Benedict, Matthias Kirchhoff, Michèle Schaub, Michael Gluch and Sandro Fischer, Energy-efficient Ship Operation - The Concept of Green Manoeuvring -- Ioannis Oikonomou, Aspasia Pastra and Ilias Visvikis, A Financial Business Case for Corporate Social Responsibility -- Momoko Kitada and Pamela Tansey, Impacts of CSR on Women in the Maritime Sector -- Michael Ekow Manuel, Safety and Risk Management Considerations for CSR -- Jan Skovgaard, Response to institutional processes - A study of Corporate Social Responsibility in Danish shipping companies.
Law and Criminology
text file PDF
Keywords: Law of the sea; International law; Social responsibility of business